THE MAIN DIFFERENCES BETWEEN UK AND US ENGLISH - Ubaydullayeva B.Oʼ; Abdumoʼminova Noila (TADQIQOTLAR, 2025)
Abstract This article explores key differences between British English and American English based on their spelling, grammar, pronunciation , and vocabulary as well. It also gives some data about historical and cultural reasons to this case and the development of the English language in the United States after its separation from Britain. Through detailed examples , the article regards how linguistic evolution and external influences contributed this distinct. Understanding these differences is essential for effective inernational communication and language learning.